2015
DOI: 10.1267/ahc.14046
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Core Planar Cell Polarity Proteins, PRICKLEs, in Ameloblasts of Rat Incisors: Possible Regulation of Enamel Rod Decussation

Abstract: To confirm the possible involvement of planar cell polarity proteins in odontogenesis, one group of core proteins, PRICKLE1, PRICKLE2, PRICKLE3, and PRICKLE4, was examined in enamel epithelial cells and ameloblasts by immunofluorescence microscopy. PRICKLE1 and PRICKLE2 showed similar localization in the proliferation and secretory zones of the incisor. Immunoreactive dots and short rods in ameloblasts and stratum intermedium cells were evident in the proliferation to differentiation zone, but in the secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…In this study, Prickle3, a planar cell polarity protein, RhoA, prototypical Rho GTPases have shown to have an integral role in cytoskeletal arrangement, membrane-trafficking pathways, and ECM interactions, which are all crucial steps for cell polarization [ 31 ]. Interestingly, the expression of RhoA in our study showed the same trend as Prickle3, which has shown to be positively expressed in papillary layer cells and some singular cells adjacent to the dentin [ 6 ] In our previous study, we examined the role of RhoA on the migration of human dental papilla cells using RhoA mutant adenoviruses and found that RhoA activity could active JNK signaling [ 14 ]. In the present study, JNK inhibitor treatment down-regulated the expression of RhoA mRNA and inhibited RhoA activity.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In this study, Prickle3, a planar cell polarity protein, RhoA, prototypical Rho GTPases have shown to have an integral role in cytoskeletal arrangement, membrane-trafficking pathways, and ECM interactions, which are all crucial steps for cell polarization [ 31 ]. Interestingly, the expression of RhoA in our study showed the same trend as Prickle3, which has shown to be positively expressed in papillary layer cells and some singular cells adjacent to the dentin [ 6 ] In our previous study, we examined the role of RhoA on the migration of human dental papilla cells using RhoA mutant adenoviruses and found that RhoA activity could active JNK signaling [ 14 ]. In the present study, JNK inhibitor treatment down-regulated the expression of RhoA mRNA and inhibited RhoA activity.…”
Section: Discussionmentioning
confidence: 56%
“…MAP1B [ 5 ], PRICKLEs [ 6 ], and Celsr1 [ 7 ] have been considered as essential polarity proteins localized in the odontoblastic layer C-Jun N-terminal kinase (JNK) kinase, which affects the spine morphology [ 8 ], regulates the expression of polarity complex genes Celsr2, Numb, Prkcz, Llgl2 in bone marrow hematopoietic progenitor cells [ 9 ]. Furthermore, previous studies have shown that JNK signaling participates in cell proliferation, differentiation, apoptosis, and cytoskeleton reorganization [ 10 12 ], and regulates plane cell polarity (PCP) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this variant is also ∼300 kb upstream of PRICKLE2, a planar cell polarity protein involved in amelogenesis. In rats, Prickle2 in rats is expressed in the differentiating inner enamel epithelial cells and early inner enamel-secretory ameloblasts (29).…”
Section: Tooth Agenesis Impaction and Rotationmentioning
confidence: 99%
“…Amelogenesis: Similar to dentinogenesis, in amelogenesis many different factors have also effects on enamel secretion and/or mineralization, thus we design again a Table where the factors are classified according to its role in secretion and/or mineralization (Table 4) [50,52,67,77,83,98,100,103,119,126,[128][129][130][131][132][133][134].…”
Section: Dentinogenesismentioning
confidence: 99%